Survival Prognostic Factors of Non-Invasive Ventilation in Amyotrophic Lateral Sclerosis: A Systematic Review - Aleksandra Orlova; Yaroslav Malygin; Anna Gofman; Sofija Sotulenko; Veronika Gandalian; Ioan Kartashov; Lev Brylev; Sergey Bolevich; Tamara Nikolic Turnic; Vladimir Jakovljevic (Life)
Objective: Amyotrophic lateral sclerosis is a neurodegenerative disease with high rates of disability and mortality. Non-invasive ventilation (NIV) is an effective method of treating patients, increasing life expectancy, but currently, predictors available to determine the best outcome of therapy in this category of patients are unknown. This systematic review aimed to determine the impact of prognostic factors on benefits from NIV application compared with non-NIV tools of treatment (invasive ventilation and standard care) in case of survival of ALS patients. Method: We systematically sought relevant longitudinal cohort and case-control studies published in PubMed, CINAHL/EMBASE, Cochrane library, and Scopus. Results: We included seven prospective studies, published in 2010–2020, in the analysis. According to the evidence base available to date, NIV favors survival compared to non-NIV in patients with bulbar onset ALS. We obtained conflicting data on the significance of spinal onset and bulbar function. Survival depending on patient age, and also for spinal, cervical, and flail limb phenotypes during NIV therapy has not been sufficiently studied and needs further investigation. Conclusions: The studies analyzed in this review allow us to state with confidence that NIV is effective in bulbar onset ALS, taking into account recommendations for duration of ventilation and the use of the full range of symptomatic therapy, including mechanically assisted coughing. The effectiveness of NIV on severe bulbar symptoms requires further research.